Genetic Basis of Natural Variation in Spontaneous Grooming in Drosophila melanogaster. - Yanagawa, A.; Huang, W.; Yamamoto, A.; Wada-Katsumata, A.; Schal, C.; Mackay, T.F.C. (G3 : genes - genomes - genetics, 2020)
Spontaneous grooming behavior is a component of insect fitness. We quantified spontaneous grooming behavior in 201 sequenced lines of the Drosophila melanogaster Genetic Reference Panel and observed significant genetic variation in spontaneous grooming, with broad-sense heritabilities of 0.25 and 0.24 in females and males, respectively. Although grooming behavior is highly correlated between males and females, we observed significant sex by genotype interactions, indicating that the genetic basis of spontaneous grooming is partially distinct in the two sexes. We performed genome-wide association analyses of grooming behavior, and mapped 107 molecular polymorphisms associated with spontaneous grooming behavior, of which 73 were in or near 70 genes and 34 were over 1 kilobase from the nearest gene. The candidate genes were associated with a wide variety of gene ontology terms, and several of the candidate genes were significantly enriched in a genetic interaction network. We performed functional assessments of 29 candidate genes using RNA interference, and found that 11 affected spontaneous grooming behavior. The genes associated with natural variation in Drosophila grooming are involved with glutamate metabolism (Gdh) and transport (Eaat); interact genetically with (CCKLR-17D1) or are in the same gene family as (PGRP-LA) genes previously implicated in grooming behavior; are involved in the development of the nervous system and other tissues; or regulate the Notch and Epidermal growth factor receptor signaling pathways. Several DGRP lines exhibited extreme grooming behavior. Excessive grooming behavior can serve as a model for repetitive behaviors diagnostic of several human neuropsychiatric diseases.